The traditional uses, secondary metabolites, and pharmacology of Symplocos species - Giang, Le Thi; Thao, Vu Mai; Oanh, Nguyen Tu; Nhung , Vu Phuong; Hang, Nguyen Thi Minh; Ban, Ninh Khac; Nhiem, Nguyen Xuan (Vietnam Journal of Science and Technology, 2025)
Ethnopharmacological relevance: The genus Symplocos (Symplocaceae family) includes 500 accepted names and is distributed in tropical and subtropical regions. Some Symplocos species are used in traditional medicines for the treatment of bacterial diseases, hemorrhage, gynecological disorders, and live diseases.Aim of the study: This review focuses on the phytochemistry and pharmacology of Symplocos genus to understand the link between the traditional medicinal uses, phytochemistry, and bioactivities. Thus, they provide a scientific foundation for further research in the phytochemical and pharmacological activities.Materials and methods: Information about the Symplocos genus was collected using various databases, such as Web of Science, SciFinder, Google Scholar, PubMed, Wiley, ACS publications, Elsevier, and SpringerLink between 1980 and 2024. Plant names were validated by “World of Flora Online” (www.worldfloraonline.org).Results: Up to now, total 202 compounds have been reported from Symplocos species, including triterpenoids, flavonoids, iridoids, lignans, steroids, phenolics, and athraquinones. The extracts and phytochemical constituents of the Symplocos genus are a rich source of biological activities, including anti-cancer, antioxidant, anti-inflammatory, antibacterial, hypoglycemic, and other activities.Conclusions: The review indicated that the Symplocos genus is a promising source of biological compounds, and special anti-cancer activity of chromanes. The results of this review confirm the great potential of Symplocos species. Thus, it will be helpful for further research in the phytochemistry and pharmacology of the Symplocos genus.